If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 2x + 7 = 20x + -4 Reorder the terms: 7 + 7x + 2x = 20x + -4 Combine like terms: 7x + 2x = 9x 7 + 9x = 20x + -4 Reorder the terms: 7 + 9x = -4 + 20x Solving 7 + 9x = -4 + 20x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20x' to each side of the equation. 7 + 9x + -20x = -4 + 20x + -20x Combine like terms: 9x + -20x = -11x 7 + -11x = -4 + 20x + -20x Combine like terms: 20x + -20x = 0 7 + -11x = -4 + 0 7 + -11x = -4 Add '-7' to each side of the equation. 7 + -7 + -11x = -4 + -7 Combine like terms: 7 + -7 = 0 0 + -11x = -4 + -7 -11x = -4 + -7 Combine like terms: -4 + -7 = -11 -11x = -11 Divide each side by '-11'. x = 1 Simplifying x = 1
| -4x+5-x=x-13 | | 4x+6=5x+15 | | 3-2x=133 | | 3-2x=130 | | 3(x-2)=(x-2)2 | | -4+5-x=x-13 | | 4y+3=2y-1 | | -15x^2+78x-15=0 | | (2y+1)2-(2y-1)2=16 | | 15x^2-78x-15=0 | | X(5)+y(3)=266 | | 3(x-1)+4=2(x+3)+1 | | 5(10-x)+20+6x=80 | | 3-2(x-1)=4-3(x+1) | | -8m^4-12m^3-1871m^2+636m-457=0 | | 6-3(x+1)=2+3(2x+3) | | 3(3x-2)=2(2x-5) | | -16m^4-24m^3-3742m^2+1272m-934=0 | | (4-x^2)dy-4ydx=0 | | f(t)=sin(2t)*cos(2t) | | 4(x-3)+5=9 | | 3x-3+4=6 | | 10-(50+x)=15 | | 4x+24+5x+10=6x+6+5x+20 | | 5(1-3x)=-35 | | -2(5-5x)=-40 | | 11(x+1)=99 | | 7x-1=10x-10 | | 50-2x=90-4x | | 415-5x=390 | | 3x(1-x)=3(x-3) | | 6(3-4x)=-6 |